Between Gazing and Witnessing: Feminism and Watching Women Suffer on Television - Strehlau, Nelly (Zagadnienia Rodzajów Literackich, 2020)
The present article discusses ethical aspects of the representations of (sexual) violence and (predominantly women’s) suffering in two recent television series, The Handmaid’s Tale and Dietland. It reflects on the uses and functions of violent imagery they contain and the manner in which this imagery contributes to the series’ perception as feminist shows. The primary question posed is whether this violence occasions engagement or disengagement: whether the role they cast their audiences in consists in gazing or witnessing.